Relationship of Physical Activity With Anxiety and Depression Symptoms in Chinese College Students During the COVID-19 Outbreak - Xiang, Ming-Qiang; Tan, Xian-Ming; Sun, Jian; Yang, Hai-Yan; Zhao, Xue-Ping; Liu, Lei; Hou, Xiao-Hui; Hu, Min (Frontiers in Psychology, 2020)
Introduction During the COVID-19 outbreak, many citizens were asked to stay at home in self-quarantine, which can pose a significant challenge with respect to remaining physically active and maintaining mental health. This study aimed to evaluate the prevalence of inadequate physical activity, anxiety, and depression and to explore the relationship of physical activity with anxiety and depression symptoms among Chinese college students during quarantine. Method Using a web-based cross-sectional survey, we collected data from 1,396 Chinese college students. Anxiety and depression were assessed with the Self-Rating Anxiety Scale (SAS) and the Self-Rating Depression Scale (SDS), respectively. The data on physical activity were collected by types of physical activity and the International Physical Activity Questionnaire (IPAQ-SF). Results During the COVID-19 outbreak, about 52.3% of Chinese college students had inadequate physical activity. The rates of anxiety and depression symptoms were 31.0% and 41.8%, respectively. A high level of physical activity (β = -0.121, P < 0.001) was significantly closely associated with low anxiety, while a moderate (β = -0.095, P = 0.001) or high (β = -0.179, P < 0.001) level of physical activity was significantly closely associated with reduced depression after adjusting confounding demographic factors. Moreover, specific types of physical activity, such as stretching and resistance training, were negatively correlated with both anxiety and depression; doing household chores was negatively correlated with depression. Conclusion Our findings highlight specific levels and types of home-based physical activities that need to be taken into consideration to protect the mental health of college students during the COVID-19 epidemic. Keywords: COVID-19; physical activity; anxiety; depression; college students